The effect of nitrogen fertiliser on the sensometabolomic profile of steamed potatoes : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Horticultural Science at Massey University, Manawatu, New Zealand - Ross, Sarah Beatrix (Massey University, 2020)
For growers of high-value potatoes (𝘚𝘰𝘭𝘢𝘯𝘶𝘮 𝘵𝘶𝘣𝘦𝘳𝘰𝘴𝘶𝘮 𝘓.), flavour is an important product characteristic to consider, as a driver of consumer purchasing behaviour. Recent potato flavour research has focused on combining sensory and analytical techniques to better understand flavour. However, there is a lack of understanding around the relationship between consumer flavour preferences and flavour-related composition. In addition, there is very little known about the impact of agronomic factors on these aspects combined. For nitrogen, a nutrient of concern in New Zealand because of its environmental implications, understanding on how different rates of nitrogen fertiliser affect flavour is limited. Therefore, this study used a combined approach of consumer sensory evaluation with metabolite testing (sensometabolomics) to determine if nitrogen fertiliser affects the perception of steamed gourmet potato flavour and composition. Two potato varieties, ‘Annabelle’ and ‘Andean Sunside’, were treated with three different rates of nitrogen fertiliser during crop growth: 0 kg N ha⁻¹, 150 kg N ha⁻¹, and 300 kg N ha⁻¹. One hundred and eleven regular potato consumers assessed steamed potato samples for liking, using a labelled affective magnitude scale, and flavour, using rate-all-that-apply, across 14 flavour attributes. The levels of key flavour-related metabolites and variables were measured in the same potatoes, including dry matter, sugars, glycoalkaloids, polyphenols, umami amino acids, total nitrogen, nitrate, and volatile compounds. Principal component analysis was used to assess the association between changes in composition and flavour. Nitrogen fertilisation signiﬁcantly affected composition and ﬂavour in Annabelle and Andean Sunside, and ranked liking in Andean Sunside. In both Annabelle and Andean Sun-side, total nitrogen, asparagine, and glutamine levels signiﬁcantly increased with the rate of nitrogen fertiliser applied, from 0 kg N ha⁻¹ to 300 kg N ha⁻¹. In Annabelle alone, nitrate, 2-butanone, 2-methyl-2-(E)-butenal, methional, and benzaldehyde increased with nitrogen, while dry matter and both α-solanine and α-chaconine concentrations decreased. The effect of fertiliser on β-ocimene was variable. In Andean Sunside, α-solanine, β-ocimene, and phenethyl alcohol all increased with nitrogen supply, while glucose and fructose con-centrations signiﬁcantly decreased. Levels of (Z)-hex-3-en-1-ol, linalool, and benzyl alcohol signiﬁcantly increased between 0 and 150 kg N ha⁻¹ treatments. The effect of nitrogen on quercetin-3-rutinoside was inconsistent in Andean Sunside. While average liking was not signiﬁcantly affected by nitrogen, Andean Sunside 0 kg N ha⁻¹ samples were ranked signiﬁcantly higher in liking compared to 300 kg N ha⁻¹ samples. Overall, nitrogen fertilisation appeared to slightly, but signiﬁcantly, increase the intensity of attributes with more negative associations. Annabelle 300 kg N ha⁻¹ samples contained signiﬁcantly higher intensities of nutty, musty, and sour attributes, while Andean Sunside 0 kg N ha⁻¹ samples were signiﬁcantly more buttery, and less cardboard and green grass-ﬂavoured, compared to 150 kg N ha⁻¹ samples. Therefore, for Annabelle, either 0 and 150 kg N ha⁻¹ treatments were recommended to reduce the intensity of off-ﬂavoured attributes. For Andean Sunside, decreasing the rate of nitrogen applied was recommended to reduce the intensity of off-ﬂavours and increase the intensity of buttery ﬂavour, as observed in 0 kg N ha⁻¹ samples. Changes in composition could not be associated with changes in perceived ﬂavour, within the varieties and treatments used in this study.
Figures are re-used with permission.
Keywords: 300404 Crop and pasture biochemistry and physiology; 300899 Horticultural production not elsewhere classified